Lipid dysregulation in mouse ovarian antral follicles after oral exposure to a human relevant mixture of three phthalates - Kara L. Miller; Taylor Massey; Vivianna Metzler; Amanda Adams; Xiaosong Liu; Kimberlie Burns; Lydia R. Porter; Justin Snider; Zelieann R. Craig (Toxicology, 2026)

Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Occurrence, patterns and previously overlooked sources of three veterinary ectoparasiticides in rural and urban Welsh rivers - Molly Hadley; Laura Rodwell; Matt Stewart; Daniel Crowther; Jasper Linley-Adams; Sian Craig; Suzanne Thomas; Anthony Gravell; Isabelle Durance; Ian P. Vaughan; S.J. Ormerod (Environmental Pollution, 2026)

Shell trace elemental fingerprints of the deep-sea methane seep mussel Gigantidas childressi vary by depth, site, and shell growth region - Ian J. Grace; Luciana Génio; David B. Eggleston; Brandon J. Puckett; F. Joel Fodrie; Adam N.H. Smith; Craig M. Young (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Relative importance of climate versus socio-environmental development changes to 2050 in rural coastal Bangladesh—a system analysis - Attila N. Lázár; Robert J. Nicholls; Craig W. Hutton; Andres Payo; Helen Adams; Anisul Haque; Derek Clarke; Mashfiqus Salehin; Alistair Hunt; Andrew Allan; W. Neil Adger; M. Munsur Rahman; et al. (Regional Environmental Change, 2026)
Climate change and development are having a profound influence on the integrity of coastal Bangladesh’s people, economy and ecology with climate change widely considered the dominant driver. Our bespoke integrated assessment model (IAM) simulates these changes for rural areas by coupling physical models with economic models, considering shocks like cyclone landfalls, and utilising substantial primary/secondary datasets and stakeholder-derived future scenarios. As such, this study assesses the Bangladesh coastal system’s sensitivity to climate change and policy decisions to 2050. The IAM results suggest that flooding and salinisation have high sensitivity to climatic and environmental drivers, and agricultural productivity is strongly dependent on farming methods and investment in better crop varieties to counteract these changes. Inequality, poverty and GDP per capita are more sensitive to non-climatic drivers. Nonetheless, extreme climatic conditions do impact livelihoods due to economic damage with variable effects across different household types. At least over the next 25 years, development choices (i.e. concrete adaptation actions) will have a similar if not stronger influence on livelihoods and economic wellbeing in rural coastal Bangladesh than climate-driven environmental change. This IAM approach supports decision makers to identify sustainable development pathways that address both current socio-environmental vulnerability as well as develop a more climate-resilient future.

Angler Heterogeneity in Newfoundland and Labrador, Canada: Insights From Nearly Three Decades (1994–2022) of Atlantic Salmon Angler License and Activity Records - Travis E. Van Leeuwen; Michelle G. Fitzsimmons; J. Brian Dempson; Christopher W. White; Mark Young; Donald Keefe; Isabelle Schmelzer; Nicholas I. Kelly; Craig F. Purchase; Blair Adams; David Coté (Fisheries Management and Ecology, 2026)
Angler demographics and motivations are an important consideration to successful fisheries management. We examined 29 years of angler license and activity records from the recreational Atlantic salmon fishery in Newfoundland and Labrador, Canada to: (1) provide a contemporary evaluation of angler demographic trends; (2) evaluate age and regional differences between anglers who prioritized retention versus catch‐and‐release; and (3) discuss how various management and COVID restrictions affected angler participation and activity. Resident license holders made up 91.3% of total licenses purchased. The average age of license holders increased from 39 years of age in 1994 to 54 years of age in 2022, with 6–20 year olds making up

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Marine exploitation and the arrival of farming: resolving the paradox of the Mesolithic-Neolithic transition in Denmark - T. Rowan McLaughlin; Harry K. Robson; Rikke Maring; Adam Boethius; Eric Guiry; Daniel Groß; Satu Koivisto; Bente Philippsen; Nicky Milner; Geoff Bailey; Oliver E. Craig (Quaternary Science Reviews, 2025)

Community-based mangrove restoration following a catastrophic hurricane in The Bahamas - Justin P. Lewis; Sean T. Giery; Keith A. Rossin; Kyle A. Rossin; Jordan R. Cissell; Michael K. Steinberg; Nina L. Sanchez; Aaron J. Adams; Craig A. Layman (Wetlands Ecology and Management, 2025)
Restoration of damaged coastal ecosystems is a component of broader conservation strategies. Hurricane Dorian (September 2019) was the worst natural disaster in the history of The Bahamas. This caused widespread societal and ecological damage, including destroying mangrove ecosystems—systems that provide numerous ecosystem services for the country. We first used satellite mapping to document mangrove destruction caused by Dorian. Second, several local, national, and international partners organized to spearhead community-based mangrove planting initiatives that resulted in more than 101,560 trees planted as of December 2024. We carried out a field experiment with the plantings to examine the effects of tree age (propagule vs. seedling), spacing design (clumped vs. spaced), and plant source (The Bahamas vs. Florida). Seedling survival was 4.5 × that of propagules—but at a greater time and financial cost—indicating that a combination of planting propagules and seedlings may be a preferred restoration approach. No effect of clumped vs. spaced distribution was found. This suggests other factors, e.g., nutrient limitation or hydroperiod, drive the success of plantings. Source effects (whether propagules were collected from, and grown to seedlings in, The Bahamas or Florida) influenced seedling survival and growth and had an influence similar in magnitude to local patch-scale environmental variation. The need for ecosystem restoration following Hurricane Dorian and the willingness of more than 2,000 community individuals to contribute made possible the scale and scope of this project. These findings will help guide this community-based initiative and it will inform similar restoration efforts in other regions.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Delphinid postmortem vitreous humor biochemistry as proxy for antemortem blood analyte concentrations - Tiffany Zorotrian; Adam W. Stern; Alexander Costidis; Craig A. Harms; Hanzhi Gao; Christine Fontaine; Hayley R. Adams (Marine Mammal Science, 2025)

Contrasting species-specific stress response to environmental pH determines the fate of coccolithophores in future oceans - Nishant Chauhan; Craig J. Dedman; Chloë Baldreki; Adam A. Dowle; Tony R. Larson; Rosalind E.M. Rickaby (Marine Pollution Bulletin, 2024)

Antimicrobial susceptibility profiles among commensal Mannheimia haemolytica and Pasteurella multocida isolated from apparently healthy sheep processed in California: Results from a cross-sectional pilot study - Wendi Jackson; Jenna Tucker; Heather Fritz; Craig Bross; Jaymes Adams; Marissa Silva; Catherine Lorenz; Edith Marshall (Preventive Veterinary Medicine, 2024)

Will They Stay or Will They Go — Understanding South Atlantic Coastal Wetland Transformation in Response to Sea-Level Rise - Michelle C. Moorman; Zachary S. Ladin; EmmaLi Tsai; Adam Smith; Amanda Bessler; Jean Richter; Rebecca Harrison; Brian Van Druten; Wendy Stanton; Chuck Hayes; Billy Wayne Harris; Mike Hoff; et al. (Estuaries and Coasts, 2024)
Threats to coastal wetlands, including sea-level rise and subsidence, led the National Wildlife Refuge (NWR) System to protect over 500,000 hectares of coastal wetlands during the twentieth century, with approximately 20% occurring in the South Atlantic geography. This effort has involved systematic long-term monitoring of changes in marsh elevation using surface elevation tables and marker horizons at 20 sites across 19 NWRs in the southeastern coastal USA. From 2012 to 2021, the rates of change in surface elevation (−9.3 to 7.1 mm/year), accretion (−0.3 to 17.5 mm/year), and net vertical elevation change (−14.3 to 3.1 mm/year) were highly variable among monitoring sites and varied with coastal wetland type (oligohaline marsh, salt marsh, pocosin, or forested wetland), land surface elevation, and estuarine salinity and geomorphology (i.e., tidally influenced or embayed). Of 20 sites included in our study, only six were gaining elevation at a rate that was equal to or greater than the long-term rates of sea-level rise and therefore considered resilient. Only Waccamaw and Currituck NWRs, both located in oligohaline marshes, were gaining elevation at a rate that exceeded sea-level rise by 1 mm/year. These results support the mounting evidence that many coastal wetlands, particularly in the South Atlantic geography of the USA, will undergo ecological transformations in the next several decades. The NWR System and other coastal management entities will need to use strategic decision-making frameworks to identify management actions that can mitigate the loss of coastal wetlands to support the conservation of coastal wetland–dependent and obligate species.

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

The influence of habitat alteration is widespread, but the impact of climate cannot continue to be discounted - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)

Surface-layer turbulence associated with a fast spreading grass fire - Shiyuan Zhong; Melissa Gonzalez-Fuentes; Craig B. Clements; Xindi Bian; Warren E. Heilman; Joseph J. Charney; Mario M. Valero; Adam K. Kochanski; Michael T. Kiefer (Agricultural and Forest Meteorology, 2024)

Habitat alteration or climate: What drives the densities of an invading ungulate? - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)
Anthropogenic habitat alteration and climate change are two well‐known contributors to biodiversity loss through changes to species distribution and abundance; yet, disentangling the effects of these two factors is often hindered by their inherent confound across both space and time. We leveraged a contrast in habitat alteration associated with the jurisdictional boundary between two Canadian provinces to evaluate the relative effects of spatial variation in habitat alteration and climate on white‐tailed deer ( Odocoileus virginianus ) densities. White‐tailed deer are an invading ungulate across much of North America, whose expansion into Canada's boreal forest is implicated in the decline of boreal caribou ( Rangifer tarandus caribou ), a species listed as Threatened in Canada. We estimated white‐tailed deer densities using 300 remote cameras across 12 replicated 50 km 2 landscapes over 5 years. White‐tailed deer densities were significantly lower in areas where winter severity was higher. For example, predicted deer densities declined from 1.83 to 0.35 deer/km 2 when winter severity increased from the lowest value to the median value. There was a tendency for densities to increase with increasing habitat alteration; however, the magnitude of this effect was approximately half that of climate. Our findings suggest that climate is the primary driver of white‐tailed deer populations; however, understanding the mechanisms underpinning this relationship requires further study of over‐winter survival and fecundity. Long‐term monitoring at the invasion front is needed to evaluate the drivers of abundance over time, particularly given the unpredictability of climate change and increasing prevalence of extreme weather events.

Community size‐spectra applied to recreational freshwater fisheries in Puerto Rican reservoirs - Brent A. Murry; María de Lourdes Olmeda; Craig Lilyestrom; Daniel S. Adams; Katherine Adase; Miguel García‐Bermudez (Fisheries Management and Ecology, 2024)
We developed a management framework based on community size‐spectra (CSS) to establish targets to maximize desirable gamefish. We evaluated the influence of relative abundance of fish functional groups and watershed characteristics on the slope of the CSS or ecological efficiency. Both ecological efficiency and capacity were strongly influenced by relative abundance of fish functional groups and the degree of water level variation. Steeper slopes indicated overfished gamefish populations, whereas flatter slopes indicated systems dominated by undesirable invasive large‐bodied low trophic position fish. We hypothesize that a desirable fishery would have a target range of CSS slopes that provides a deterministic community‐based framework of predictable responses to environmental and food web changes that can be used to evaluate outcomes of management actions and a means to assess annual progress toward desirable conditions.

A practice quit model to test early efficacy of medications for alcohol use disorder in a randomized clinical trial - Lara A. Ray; Wave-Ananda Baskerville; Steven J. Nieto; Erica Grodin; Craig Enders; Annabel Kady; Lindsay Meredith; Artha Gillis; Adam Leventhal; Diana Ho; Karen Miotto (Psychopharmacology, 2024)

The interactive impacts of a constant reef stressor, ultraviolet radiation, with environmental stressors on coral physiology - Adam T. Downie; Rebecca L. Cramp; Craig E. Franklin (Science of The Total Environment, 2024)

Sublethal consequences of ultraviolet radiation exposure on vertebrates: Synthesis through meta‐analysis - Adam T. Downie; Nicholas C. Wu; Rebecca L. Cramp; Craig E. Franklin (Global Change Biology, 2023)
Ultraviolet radiation (UVR) from the sun is a natural daytime stressor for vertebrates in both terrestrial and aquatic ecosystems. UVR effects on the physiology of vertebrates manifest at the cellular level, but have bottom‐up effects at the tissue level and on whole‐animal performance and behaviours. Climate change and habitat loss (i.e. loss of shelter from UVR) could interact with and exacerbate the genotoxic and cytotoxic impacts of UVR on vertebrates. Therefore, it is important to understand the range and magnitude of effects that UVR can have on a diversity of physiological metrics, and how these may be shaped by taxa, life stage or geographical range in the major vertebrate groups. Using a meta‐analytical approach, we used 895 observations from 47 different vertebrate species (fish, amphibian, reptile and bird), and 51 physiological metrics (i.e. cellular, tissue and whole‐animal metrics), across 73 independent studies, to elucidate the general patterns of UVR effects on vertebrate physiology. We found that while UVR's impacts on vertebrates are generally negative, fish and amphibians were the most susceptible taxa, adult and larvae were the most susceptible life stages, and animals inhabiting temperate and tropical latitudes were the most susceptible to UVR stress. This information is critical to further our understanding of the adaptive capacity of vulnerable taxon to UVR stress, and the wide‐spread sublethal physiological effects of UVR on vertebrates, such as DNA damage and cellular stress, which may translate up to impaired growth and locomotor performance. These impairments to individual fitness highlighted by our study may potentially cause disruptions at the ecosystem scale, especially if the effects of this pervasive diurnal stressor are exacerbated by climate change and reduced refuge due to habitat loss and degradation. Therefore, conservation of habitats that provide refuge to UVR stress will be critical to mitigate stress from this pervasive daytime stressor.

Interplay of legacy irrigation and nitrogen fertilizer inputs to spatial variability of arsenic and uranium within the deep vadose zone - Arindam Malakar; Chittaranjan Ray; Matteo D'Alessio; Jordan Shields; Craig Adams; Marty Stange; Karrie A. Weber; Daniel D. Snow (Science of The Total Environment, 2023)

Guidelines for the selection of corrosion resistant alloys for CCS and CCUS injection wells - Bruce Craig; Adam Rowe; Michael Warmack; Thomas E. Doll; Catherine Stevens; Kevin C. Connors (International Journal of Greenhouse Gas Control, 2023)

Acute and chronic toxicity of manganese to tropical adult coral (Acropora millepora) to support the derivation of marine manganese water quality guideline values - Lisa A. Golding; Monique T. Binet; Merrin S. Adams; Justin Hochen; Craig A. Humphrey; Gwilym A.V. Price; Amanda J. Reichelt-Brushett; Matthew Salmon; Jenny L. Stauber (Marine Pollution Bulletin, 2023)

Precision of the Abaxis VetScan VS2 for postmortem biochemical analysis of delphinid vitreous humor - Tiffany Zorotrian; Adam W. Stern; Hanzhi Gao; Alexander Costidis; Christine Fontaine; Alissa Deming; Craig Harms; Hayley R. Adams (Marine Mammal Science, 2023)
Biochemical analysis of vitreous humor has several forensic applications, including toxicology, estimation of the postmortem interval, and as proxy for select antemortem serum analytes. Estimation of postmortem interval from vitreous humor analytes such as potassium has potential to be a valuable forensic tool for marine mammal strandings, as time of death is essential to provide spatial and temporal context for anthropogenic interactions. The Abaxis VetScan VS2 (VetScan) chemistry analyzer is inexpensive, compact, and requires low sample volume (100 μl), making it ideal for organizations with limited resources and limited samples. This pilot study compared accuracy of the Vetscan on delphinid serum/plasma ( n = 7) to the Beckman Coulter AU480, validated the precision of the Vetscan for biochemical analysis of delphinid vitreous humor using the described sample processing protocol, and assessed analyte stability at room temperature in delphinid vitreous humor. Pooled samples ( n = 12) of delphinid vitreous humor were serially analyzed and the between‐run and within‐run coefficient of variation of the VetScan was acceptable for most analytes tested but was not for creatinine, total bilirubin, amylase, and alanine aminotransferase. These results demonstrated the precision of the VetScan for the analysis of glucose, albumin, globulin, total protein, urea nitrogen, sodium, potassium, calcium, and phosphorus in delphinid vitreous humor.

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

Long-term data reveal equivocal evidence for intraguild suppression among sympatric canids - Javan M. Bauder; Maximilian L. Allen; Adam A. Ahlers; Thomas J. Benson; Craig A. Miller; Kirk W. Stodola (Biodiversity and Conservation, 2022)

Diurnal increases in depths of humpback whale ( Megaptera novaeangliae ) mother‐calf pods off West Maui, Hawaiʻi: A response to vessels? - Adam A. Pack; James O. Waterman; Alison S. Craig (Marine Mammal Science, 2022)
Studies of humpback whale ( Megaptera novaeangliae ) habitat use in their Hawaiian breeding grounds have revealed that mother‐calf pairs favor shallow waters to avoid harassment from males. However, human activity in these same waters may exert an opposing force on habitat use. To investigate this hypothesis, instantaneous scan samples of whale and vessel distribution were collected from West Maui, Hawaiʻi. Theodolite position fixes were combined with GIS techniques to determine the depths and seabed terrain type occupied by 161 humpback whale pods containing a calf (calf pods) and 872 pods without a calf (noncalf pods). We found no significant diurnal trends for noncalf pods, but calf pods occupied progressively deeper water over the course of each day. There was no evidence that this shift was related to (1) a “spillover” resulting from high mother‐calf density in shallow water, (2) harassment by males occupying the same space as mother‐calf pairs, or (3) the presence of mainly older and larger calves. However, while diurnal trends of whale‐watching vessels largely mirrored those of mother‐calf pods, nonwhale‐watching vessels tended to remain in shallower waters throughout the day. These results suggest that nearshore vessels may negatively impact the natural preference of mother‐calf pairs for shallow waters.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Whole genome resequencing reveals signatures of rapid selection in a virus‐affected commercial fishery - Owen J. Holland; Madeline Toomey; Collin Ahrens; Ary A. Hoffmann; Laurence J. Croft; Craig D. H. Sherman; Adam D. Miller (Molecular Ecology, 2022)
Infectious diseases are recognized as one of the greatest global threats to biodiversity and ecosystem functioning. Consequently, there is a growing urgency to understand the speed at which adaptive phenotypes can evolve and spread in natural populations to inform future management. Here we provide evidence of rapid genomic changes in wild Australian blacklip abalone ( Haliotis rubra ) following a major population crash associated with an infectious disease. Genome scans on H . rubra were performed using pooled whole genome resequencing data from commercial fishing stocks varying in historical exposure to haliotid herpesvirus‐1 (HaHV‐1). Approximately 25,000 single nucleotide polymorphism loci associated with virus exposure were identified, many of which mapped to genes known to contribute to HaHV‐1 immunity in the New Zealand pāua ( Haliotis iris ) and herpesvirus response pathways in haliotids and other animal systems. These findings indicate genetic changes across a single generation in H . rubra fishing stocks decimated by HaHV‐1, with stock recovery potentially determined by rapid evolutionary changes leading to virus resistance. This is a novel example of apparently rapid adaptation in natural populations of a nonmodel marine organism, highlighting the pace at which selection can potentially act to counter disease in wildlife communities.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Resource exploitation efficiency collapses the home range of an apex predator - Melanie Dickie; Robert Serrouya; Tal Avgar; Philip McLoughlin; R. Scott McNay; Craig DeMars; Stan Boutin; Adam T. Ford (Ecology, 2022)
Optimizing energy acquisition and expenditure is a fundamental trade‐off for consumers, strikingly reflected in how mobile organisms use space. Several studies have established that home range size decreases as resource density increases, but the balance of costs and benefits associated with exploiting a given resource density is unclear. We evaluate how the ability of consumers to exploit their resources through movement (termed “resource exploitation”) interacts with resource density to influence home range size. We then contrast two hypotheses to evaluate how resource exploitation influences home range size across a vast gradient of productivity and density of human‐created linear features (roads and seismic lines) that are known to facilitate animal movements. Under the Diffusion Facilitation Hypothesis, linear features are predicted to lead to more diffuse space use and larger home ranges. Under the Exploitation Efficiency Hypothesis, linear features are predicted to increase foraging efficiency, resulting in less space being required to meet energetic demands and therefore smaller home ranges. Using GPS telemetry data from 142 wolves ( Canis lupus ) distributed over more than 500,000 km 2 , we found that wolf home range size was influenced by the interaction between resource density and exploitation efficiency. Home range size decreased as linear feature density increased, supporting the Exploitation Efficiency Hypothesis. However, the effect of linear features on home range size diminished in more productive areas, suggesting that exploitation efficiency is of greater importance when resource density is low. These results suggest that smaller home ranges will occur where both linear feature density and primary productivity are higher, thereby increasing regional wolf density.

Range-wide genomic scans and tests for selection identify non-neutral spatial patterns of genetic variation in a non-model amphibian species (Pelobates cultripes) - Adam Joseph Doncheff Marques; Jeffrey Owen Hanson; Miguel Camacho-Sanchez; Iñigo Martínez-Solano; Craig Moritz; Pedro Tarroso; Guillermo Velo-Antón; Ana Veríssimo; Sílvia Benoliel Carvalho (Conservation Genetics, 2022)

Mitigation translocation as a management tool - Holly S. Bradley; Sean Tomlinson; Michael D. Craig; Adam T. Cross; Philip W. Bateman (Conservation Biology, 2022)
Mitigation translocation is a subgroup of conservation translocation, categorized by a crisis‐responsive time frame and the immediate goal of relocating individuals threatened with death. However, the relative successes of conservation translocations with longer time frames and broader metapopulation‐ and ecosystem‐level considerations have been used to justify the continued implementation of mitigation translocations without adequate post hoc monitoring to confirm their effectiveness as a conservation tool. Mitigation translocations now outnumber other conservation translocations, and understanding the effectiveness of mitigation translocations is critical given limited global conservation funding especially if the mitigation translocations undermine biodiversity conservation by failing to save individuals. We assessed the effectiveness of mitigation translocations by conducting a quantitative review of the global literature. A total of 59 mitigation translocations were reviewed for their adherence to the adaptive scientific approach expected of other conservation translocations and for the testing of management options to continue improving techniques for the future. We found that mitigation translocations have not achieved their potential as an effective applied science. Most translocations focused predominantly on population establishment‐ and persistence‐level questions, as is often seen in translocations more broadly, and less on metapopulation and ecosystem outcomes. Questions regarding the long‐term impacts to the recipient ecosystem (12% of articles) and the carrying capacity of translocation sites (24% of articles) were addressed least often, despite these factors being more likely to influence ultimate success. Less than half (47%) of studies included comparison of different management techniques to facilitate practitioners selecting the most effective management actions for the future. To align mitigation translocations with the relative success of other conservation translocations, it is critical that future mitigation translocations conform to an established experimental approach to improve their effectiveness. Effective mitigation translocations will require significantly greater investment of time, expertise, and resources in the future.

Ocean warming threatens key trophic interactions supporting a commercial fishery in a climate change hotspot - Owen J. Holland; Mary A. Young; Craig D. H. Sherman; Mun Hua Tan; Harry Gorfine; Ty Matthews; Adam D. Miller (Global Change Biology, 2021)
Worldwide, rising ocean temperatures are causing declines and range shifts in marine species. The direct effects of climate change on the biology of marine organisms are often well documented; yet, knowledge on the indirect effects, particularly through trophic interactions, is largely lacking. We provide evidence of ocean warming decoupling critical trophic interactions supporting a commercially important mollusc in a climate change hotspot. Dietary assessments of the Australian blacklip abalone ( Haliotis rubra ) indicate primary dependency on a widespread macroalgal species ( Phyllospora comosa ) which we show to be in state of decline due to ocean warming, resulting in abalone biomass reductions. Niche models suggest further declines in P . comosa over the coming decades and ongoing risks to H . rubra . This study highlights the importance of studies from climate change hotspots and understanding the interplay between climate and trophic interactions when determining the likely response of marine species to environmental changes.

Factors affecting settlement, growth and metamorphosis of hatchery-produced Australian blue mussel larvae - Kim Weston; Sam Jahangard; Brett A. Ingram; Adam D. Miller; Geordie Jennings; Craig D. H. Sherman (Aquaculture International, 2021)

Evidence of historical isolation and genetic structuring among broadnose sevengill sharks (Notorynchus cepedianus) from the world’s major oceanic regions - Alicia C. J. Schmidt-Roach; Christine C. Bruels; Adam Barnett; Adam D. Miller; Craig D. H. Sherman; David A. Ebert; Sebastian Schmidt-Roach; Charlene da Silva; Christopher G. Wilke; Craig Thorburn; Jeffrey C. Mangel; Juan Manuel Ezcurra; et al. (Reviews in Fish Biology and Fisheries, 2021)

Signatures of selection in a recent invasion reveal adaptive divergence in a highly vagile invasive species - Katarina C. Stuart; Adam P. A. Cardilini; Phillip Cassey; Mark F. Richardson; William B. Sherwin; Lee A. Rollins; Craig D. H. Sherman (Molecular Ecology, 2021)
A detailed understanding of population genetics in invasive populations helps us to identify drivers of successful alien introductions. Here, we investigate putative signals of selection in Australian populations of invasive common starlings, Sturnus vulgaris , and seek to understand how these have been influenced by introduction history. We used reduced representation sequencing to determine population structure, and identify Single Nucleotide Polymorphisms (SNPs) that are putatively under selection. We found that since their introduction into Australia, starling populations have become genetically differentiated despite the potential for high levels of dispersal, and that starlings have responded to selective pressures imposed by a wide range of environmental conditions across their geographic range. Isolation by distance appears to have played a strong role in determining genetic substructure across the starling's Australian range. Analyses of candidate SNPs that are putatively under selection indicated that aridity, precipitation and temperature may be important factors driving adaptive variation across the starling's invasive range in Australia. However, we also noted that the historic introduction regime may leave footprints on sites flagged as being under adaptive selection, and encourage critical interpretation of selection analyses in non‐native populations.

Speed of Thought and Speed of Feet: Examining Perceptual-Cognitive Expertise and Physical Performance in an English Football Academy - Adam L. Kelly; Mark R. Wilson; Daniel T. Jackson; Jennifer Turnnidge; Craig A. Williams (Journal of Science in Sport and Exercise, 2021)
The world’s greatest professional football players are able to execute effective tactical decisions as well as fulfil various physical demands. However, the degree to which both are associated with greater potential in a football academy is unknown. Therefore, the aim of this study was to investigate decision-making skill and physical performance as contributing factors to coach potential rankings in an English football academy. Ninety-eight outfield academy players (Foundation Development Phase [FDP] under-9 to under-11 n = 40; Youth Development Phase [YDP] under-12 to under-16 n = 58) participated in the study. They engaged in 45 film-based simulations at two occlusion phases (e.g., the visual display is cut-off at a precise time during an action), firstly “during” and secondly “post” execution, to examine decision-making skill. Participants also completed four fitness tests to examine physical performance. A classification of “higher-potentials” (top third) and “lower-potentials” (bottom third) were applied through coach rankings. Independent t -tests compared the decision-making and physical performance tests. Higher-potentials made significantly more accurate decisions within the “post” phase within the FDP ( P < 0.05) and the “during” phase within the YDP ( P < 0.05). Additionally, higher-potentials were significantly faster for the 0–30 m sprint in both the FDP and YDP ( P < 0.05), with higher-potentials within the YDP also significantly faster in the 0–10 m sprint ( P < 0.05) and jumped significantly higher in the countermovement jump ( P < 0.05). These findings indicated that greater football potential may be associated with superior perceptual-cognitive expertise and quicker sprint ability in both academy age phases, with a greater discriminatory function within the older cohort.

Improving Situational Awareness in the Arctic Ocean - Luc Rainville; Jeremy Wilkinson; Mary Ellen J. Durley; Scott Harper; Julia DiLeo; Martin J. Doble; Andrew Fleming; David Forcucci; Hans Graber; John T. Hargrove; John Haverlack; Nick Hughes; et al. (Frontiers in Marine Science, 2020)
To successfully operate in a harsh environment like the Arctic Ocean, one must be able to understand and predict how that environment will evolve over different spatial and temporal scales. This is particularly challenging given the on-going and significant environmental changes that are occurring in the region. Access to the most recent environmental information provides timely knowledge that enables ship-based operations to proceed efficiently, effectively and safely in this difficult arena. Knowledge of the evolving environmental conditions during a field campaign is critical for effective planning, optimal execution of sampling strategies, and to provide a broader context to data collected at specific times and places. We describe the collaborations and processes that enabled an operational system to be developed to provide a remote field-team, located on USCGC Healy in the Beaufort Sea, with near real-time situational awareness information regarding the weather, sea ice conditions, and oceanographic processes. The developed system included the punctual throughput of near real-time products such as satellite imagery, meteorological forecasts, ice charts, model outputs, and up to date locations of key sea ice and ocean-based assets. Science and operational users, as well as onshore personnel, used this system for real-time practical considerations such as ship navigation, and to time scientific operations to ensure the appropriate sea ice and weather conditions prevailed. By presenting the outputs of the system within the context of case studies our results clearly demonstrate the benefits that improved situational awareness brings to ship-based operations in the Arctic Ocean, both today and in the future.

Formation of the Mantoverde iron oxide-copper-gold (IOCG) deposit, Chile: insights from Fe and O stable isotopes and comparisons with iron oxide-apatite (IOA) deposits - Tristan M. Childress; Adam C. Simon; Martin Reich; Fernando Barra; Mauricio Arce; Craig C. Lundstrom; Ilya N. Bindeman (Mineralium Deposita, 2020)

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Normative Influences on Farmers’ Intentions to Practice Conservation Without Compensation - Jerry J. Vaske; Adam C. Landon; Craig A. Miller (Environmental Management, 2020)

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Local and regional scale habitat heterogeneity contribute to genetic adaptation in a commercially important marine mollusc ( Haliotis rubra ) from southeastern Australia - Adam D. Miller; Ary A. Hoffmann; Mun Hua Tan; Mary Young; Collin Ahrens; Michael Cocomazzo; Alex Rattray; Daniel A. Ierodiaconou; Eric Treml; Craig D. H. Sherman (Molecular Ecology, 2019)
Characterising adaptive genetic divergence among conspecific populations is often achieved by studying genetic variation across defined environmental gradients. In marine systems this is challenging due to a paucity of information on habitat heterogeneity at local and regional scales and a dependency on sampling regimes that are typically limited to broad longitudinal and latitudinal environmental gradients. As a result, the spatial scales at which selection processes operate and the environmental factors that contribute to genetic adaptation in marine systems are likely to be unclear. In this study we explore patterns of adaptive genetic structuring in a commercially‐ harvested abalone species ( Haliotis rubra ) from southeastern Australia, using a panel of genome‐wide SNP markers (5,239 SNPs), and a sampling regime informed by marine LiDAR bathymetric imagery and 20‐year hindcasted oceanographic models. Despite a lack of overall genetic structure across the sampling distribution, significant genotype associations with heterogeneous habitat features were observed at local and regional spatial scales, including associations with wave energy, ocean current, sea surface temperature, and geology. These findings provide insights into the potential resilience of the species to changing marine climates and the role of migration and selection on recruitment processes, with implications for conservation and fisheries management. This study points to the spatial scales at which selection processes operate in marine systems and highlights the benefits of geospatially‐informed sampling regimes for overcoming limitations associated with marine population genomic research.

Seasonal predictability of winter ENSO types in operational dynamical model predictions - Hong-Li Ren; Adam A. Scaife; Nick Dunstone; Ben Tian; Ying Liu; Sarah Ineson; June-Yi Lee; Doug Smith; Changzheng Liu; Vikki Thompson; Michael Vellinga; Craig MacLachlan (Climate Dynamics, 2019)

Antimicrobial activity of the biopolymer chitosan against Streptococcus iniae - Benjamin H. Beck; Mediha Yildirim‐Aksoy; Craig A. Shoemaker; Sidney Adam Fuller; Eric Peatman (Journal of Fish Diseases, 2019)
The antimicrobial activity and mode of action of chitosan were evaluated against Streptococcus iniae , a pathogenic Gram‐positive bacterium of fish worldwide. Cell proliferation kinetics were examined following exposure to varying concentrations of chitosan. The action of chitosan on S. iniae was also investigated by measuring agglutination activity, conductivity, and extracellular and intracellular bacterial adenosine triphosphate (ATP) levels. Chitosan exhibited antibacterial activity against S. iniae at concentrations of 0.1% and above and was lethal at a concentration of 0.4% and higher. The mechanism of antibacterial activity of chitosan at the inhibitory level of bacterial growth appears to hinge upon the interaction between chitosan and the oppositely charged bacterial surface. This interplay causes agglutination, which was readily observed grossly and microscopically. After interacting with the cell surface via adsorption, an efflux of intracellular ATP was documented, which suggests that chitosan disrupts the bacterial cell causing leakage of cytosolic contents and ultimately cell death. Results suggest chitosan may be worth evaluating as a natural alternative to antibiotic against S. iniae infection of fish.

Simultaneous Determination of Selected Trace Contaminants in Drinking Water Using Solid-Phase Extraction-High Performance Liquid Chromatography-Tandem Mass Spectrometry - Haiting Zhang; Danielle West; Honglan Shi; Yinfa Ma; Craig Adams; Todd Eichholz (Water, Air, & Soil Pollution, 2019)

Assessing Illinois Residents’ Support for Natural Recolonization of Apex Predators - Adam C. Landon; Craig A. Miller; Brent D. Williams (Environmental Management, 2019)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Implementation strategies for systematic conservation planning - Vanessa M. Adams; Morena Mills; Rebecca Weeks; Daniel B. Segan; Robert L. Pressey; Georgina G. Gurney; Craig Groves; Frank W. Davis; Jorge G. Álvarez-Romero (Ambio, 2019)

Tropical rainfall predictions from multiple seasonal forecast systems - Adam A. Scaife; Laura Ferranti; Oscar Alves; Panos Athanasiadis; Johanna Baehr; Michel Dequé; Tina Dippe; Nick Dunstone; David Fereday; Richard G. Gudgel; Richard J. Greatbatch; Leon Hermanson; et al. (International Journal of Climatology, 2019)
We quantify seasonal prediction skill of tropical winter rainfall in 14 climate forecast systems. High levels of seasonal prediction skill exist for year‐to‐year rainfall variability in all tropical ocean basins. The tropical East Pacific is the most skilful region, with very high correlation scores, and the tropical West Pacific is also highly skilful. Predictions of tropical Atlantic and Indian Ocean rainfall show lower but statistically significant scores. We compare prediction skill (measured against observed variability) with model predictability (using single forecasts as surrogate observations). Model predictability matches prediction skill in some regions but it is generally greater, especially over the Indian Ocean. We also find significant inter‐basin connections in both observed and predicted rainfall. Teleconnections between basins due to El Niño–Southern Oscillation (ENSO) appear to be reproduced in multi‐model predictions and are responsible for much of the prediction skill. They also explain the relative magnitude of inter‐annual variability, the relative magnitude of predictable rainfall signals and the ranking of prediction skill across different basins. These seasonal tropical rainfall predictions exhibit a severe wet bias, often in excess of 20% of mean rainfall. However, we find little direct relationship between bias and prediction skill. Our results suggest that future prediction systems would be best improved through better model representation of inter‐basin rainfall connections as these are strongly related to prediction skill, particularly in the Indian and West Pacific regions. Finally, we show that predictions of tropical rainfall alone can generate highly skilful forecasts of the main modes of extratropical circulation via linear relationships that might provide a useful tool to interpret real‐time forecasts.

The interactions of physical activity, exercise and genetics and their associations with bone mineral density: implications for injury risk in elite athletes - Adam J. Herbert; Alun G. Williams; Philip J. Hennis; Robert M. Erskine; Craig Sale; Stephen H. Day; Georgina K. Stebbings (European Journal of Applied Physiology, 2019)

Comparing depth and seabed terrain preferences of individually identified female humpback whales ( Megaptera novaeangliae ), with and without calf, off Maui, Hawaii - Adam A. Pack; Louis M. Herman; Alison S. Craig; Scott S. Spitz; James O. Waterman; Elia Y. K. Herman; Mark H. Deakos; Siri Hakala; Carley Lowe (Marine Mammal Science, 2018)

The effect of ammonia on canine polymorphonuclear cells - Craig R. Breheny; Richard J. Mellanby; Julie A. Hamilton; Adam G. Gow (Veterinary Research Communications, 2018)

Use of lumpfish for sea‐lice control in salmon farming: challenges and opportunities - Adam Powell; Jim W. Treasurer; Craig L. Pooley; Alex J. Keay; Richard Lloyd; Albert K. Imsland; Carlos Garcia de Leaniz (Reviews in Aquaculture, 2018)
Efficient sea‐lice control remains one of the most important challenges for the salmon farming industry. The use of wrasse (Labridae) as cleaner fish offers an alternative to medicines for sea‐lice control, but wrasse tend to become inactive in winter. Lumpfish ( Cyclopterus lumpus ) continue to feed on sea‐lice at low temperatures, and commercial production has escalated from thousands of fish in 2010 to well over 30 million juveniles deployed in 2016. However, production still relies on the capture of wild broodstock, which may not be sustainable. To meet global industry needs, lumpfish production needs to increase to reach c. 50 million fish annually and this can only come from aquaculture. We review current production methods and the use of lumpfish in sea cages and identify some of the main challenges and bottlenecks facing lumpfish intensification. Our gap analysis indicates that the areas in most need of research include better control of maturation for year‐round production; formulation of appropriate diets; artificial selection of elite lines with desirable traits; and development of vaccines for certified, disease‐free juvenile production. The welfare of farmed lumpfish also needs to be better quantified, and more information is needed on optimal densities and tank design. Finally, the risk of farmed lumpfish escaping from net pens needs to be critically assessed, and we argue that it might be beneficial to recover cleaner fish from salmon cages after the production cycle, perhaps using them as broodstock, for export to the Asian food markets or for the production of animal feeds.

An extreme negative Indian Ocean Dipole event in 2016: dynamics and predictability - Bo Lu; Hong-Li Ren; Adam A. Scaife; Jie Wu; Nick Dunstone; Doug Smith; Jianghua Wan; Rosie Eade; Craig MacLachlan; Margaret Gordon (Climate Dynamics, 2018)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Louis M. Herman 1930–2016 - Adam A. Pack; Elia Y. K. Herman; C. Scott Baker; Gordon B. Bauer; Phillip J. Clapham; Richard C. Connor; Alison S. Craig; Paul H. Forestell; Adam S. Frankel; Giuseppe Notarbartolo di Sciara; Matthias Hoffmann‐Kuhnt; Eduardo Mercado; et al. (Marine Mammal Science, 2017)

Tests of ecogeographical relationships in a non-native species: what rules avian morphology? - Adam P. A. Cardilini; Katherine L. Buchanan; Craig D. H. Sherman; Phillip Cassey; Matthew R. E. Symonds (Oecologia, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Vessel diameter and related hydraulic traits of 31 Eucalyptus species arrayed along a gradient of water availability - Sebastian Pfautsch; Craig Macfarlane; Marco Harbusch; Anita Wesolowski; Renee Smith; Matthias Boer; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology, 2016)
We present two comprehensive data sets that describe xylem vessel diameters and related sapwood traits for species of Eucalyptus from arid and semi‐arid woodlands and forests in Australia. Between 2009 and 2014, sapwood of mature trees was sampled in south‐western, south‐eastern and eastern Australia. One additional species was sampled from tropical north‐western Australia. The first data set describes samples collected from the basal stem section (130 cm above ground) of three individuals of 31 species of which eight species were replicated at sites that differed in climatic conditions. The second data set describes vessel characteristics of three trees from each of 10 species that were sampled at 8 m below the tree apex. The sampled trees of these 10 species are also part of the first data set. In total, we report diameters (D) for over 25 100 vessels, from 494 digital images taken from 117 trees. We also report vessel frequencies, void‐to‐wood ratios, sapwood densities and hydraulically weighted vessel diameters (Dh). Supporting data of the first data set include tree diameter at breast height (130 cm above ground), tree height, sample locations, and summary climate data. In this data set, diameter of individual vessels ranges from 10 to over 300 μm, and vessel frequency from 360 to 9070 vessels cm −2 . Wood density ranges from 0.47 to 0.96 g cm −3 . Void‐to‐wood ratio ranges from 6% to 27% and Dh ranges from 46 to 236 μm. Mean annual rainfall (P) at sample sites ranges from 246 to 2274 mm and FAO 56 reference evaporation (E) from 777 to 2110 mm. The aridity index (E/P) ranges from 0.15 to 2.93 (dimensionless). Tree diameters range from 9 to 90 cm and tree heights range from 6 to 70 m. D and Dh in the second data set range from 11 to 271 and 68 to 205 μm, respectively. These datasets will make a valuable contribution to future continental‐scale and global‐scale studies of the relationship between xylem hydraulic architecture and climate. The data sets are unique in the sense that they are phylogenetically constrained, allowing in‐depth assessment of plasticity of hydraulic attributes within a single tree genus.

Climate determines vascular traits in the ecologically diverse genus Eucalyptus - Sebastian Pfautsch; Marco Harbusch; Anita Wesolowski; Renee Smith; Craig Macfarlane; Mark G. Tjoelker; Peter B. Reich; Mark A. Adams (Ecology Letters, 2016)
Current theory presumes that natural selection on vascular traits is controlled by a trade‐off between efficiency and safety of hydraulic architecture. Hence, traits linked to efficiency, such as vessel diameter, should show biogeographic patterns; but critical tests of these predictions are rare, largely owing to confounding effects of environment, tree size and phylogeny. Using wood sampled from a phylogenetically constrained set of 28 Eucalyptus species, collected from a wide gradient of aridity across Australia, we show that hydraulic architecture reflects adaptive radiation of this genus in response to variation in climate. With increasing aridity, vessel diameters narrow, their frequency increases with a distribution that becomes gradually positively skewed and sapwood density increases while the theoretical hydraulic conductivity declines. Differences in these hydraulic traits appear largely genotypic in origin rather than environmentally plastic. Data reported here reflect long‐term adaptation of hydraulic architecture to water availability. Rapidly changing climates, on the other hand, present significant challenges to the ability of eucalypts to adapt their vasculature.

Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms - Robert W. Sanders; Sandra L. Cooke; Janet M. Fischer; Samuel B. Fey; Adam W. Heinze; Wade H. Jeffrey; Amy L. Macaluso; Robert E. Moeller; Donald P. Morris; Patrick J. Neale; Mark H. Olson; J. Dean Pakulski; et al. (Limnology and Oceanography, 2015)
Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA 320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1 , 3.0 mg L −1 , and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA 320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA 320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA 320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.

Simultaneous detection of perchlorate and bromate using rapid high-performance ion exchange chromatography–tandem mass spectrometry and perchlorate removal in drinking water - Danielle M. West; Ruipu Mu; Sanjeewa Gamagedara; Yinfa Ma; Craig Adams; Todd Eichholz; Joel G. Burken; Honglan Shi (Environmental Science and Pollution Research, 2015)

Relating water use to morphology and environment of Nothofagus from the world’s most southern forests - Sebastian Pfautsch; Pablo L. Peri; Craig Macfarlane; Floris van Ogtrop; Mark A. Adams (Trees, 2014)

The Immune System in Stroke: Clinical Challenges and Their Translation to Experimental Research - Craig J. Smith; Catherine B. Lawrence; Beatriz Rodriguez-Grande; Krisztina J. Kovacs; Jesus M. Pradillo; Adam Denes (Journal of Neuroimmune Pharmacology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Effects of Device and Formulation on In Vitro Performance of Dry Powder Inhalers - Wallace P. Adams; Sau L. Lee; Robert Plourde; Robert A. Lionberger; Craig M. Bertha; William H. Doub; Jean-Marc Bovet; Anthony J. Hickey (The AAPS Journal, 2012)

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Foraging segregation and genetic divergence between geographically proximate colonies of a highly mobile seabird - Anne E. Wiley; Andreanna J. Welch; Peggy H. Ostrom; Helen F. James; Craig A. Stricker; Robert C. Fleischer; Hasand Gandhi; Josh Adams; David G. Ainley; Fern Duvall; Nick Holmes; Darcy Hu; et al. (Oecologia, 2012)

Estimating the potential economic impacts of climate change on Southern California beaches - Linwood Pendleton; Philip King; Craig Mohn; D. G. Webster; Ryan Vaughn; Peter N. Adams (Climatic Change, 2011)

Public Lands Management Issues - Patrick Davis; Robert Malmsheimer; Eddie Bevilacqua; Terry Haines; Craig Wilcox; Robert Lefevre; Dan Rees; Tom St. Clair; Eric Miller; Terry Craigg; Paul Adams; Douglas Osborne; et al. (Journal of Forestry, 2011)
389Humans are responsible for nearly seventy thousand wildfires in the US each year, and human-caused fires have burned more than 2 million acres in five of the past ten years. Wildfires are a major contributor to US greenhouse gas emissions, adding 126.4 million metric tons of carbon dioxide into the atmosphere each year. These emissions can be significantly reduced with improved wildfire management strategies. This research examines the connection between human-caused fire proximity to physical characteristics, criminal activities, and other factors within National Forests. It presents a spatial pattern model that predicts the likelihood of fire ignition location based on physical attributes, such as: the spatial location of fire ignition crimes and other crimes on national forests, and the spatial location of national forest physical characteristics (e.g., roads, trails, recreational/unique resources, etc.). This research will present natural resource managers with practical applications of spatial analysis techniques utilizing GIS, as well as help public land managers target and deploy personnel in areas most prone to human fire ignitions during times of high fire risk.

Resightings of humpback whales in Hawaiian waters over spans of 10–32 years: Site fidelity, sex ratios, calving rates, female demographics, and the dynamics of social and behavioral roles of individuals - Louis M. Herman; Adam A. Pack; Kathryn Rose; Alison Craig; Elia Y. K. Herman; Siri Hakala; Aliza Milette (Marine Mammal Science, 2011)
From a database of approximately 5,000 Hawaiian humpback whales identified photographically between 1976 and 2010, we extracted 71 males and 39 females having resighting spans of 10 or more years, from first to most recent sighting. Findings included: (1) the male‐biased sex ratio was like that found in breeding grounds worldwide; (2) the mean span for males of 20.7 yr (maximum = 32 yr) did not differ significantly from the mean of 19.8 yr (maximum = 29 yr) for females, but males were seen in significantly more years during their spans than were females; (3) the mean number of females seen with and without calf across 11 three‐year intervals from 1977 to 2009 did not differ significantly; (4) the calving rate for the 39 females was 0.48 and seven females produced two to eight calves over spans of 22–26 yr; (5) females attracted significantly more escorts in years without calf than in years with calf; (6) individuals showed great diversity in the social units they occupied over their sighting spans, but with the most frequently observed unit for both sexes being the trio of mother, calf, and escort. Males were also observed frequently in competitive groups centered about a female without calf.

Genomic variations define divergence of water/wildlife‐associated Campylobacter jejuni niche specialists from common clonal complexes - Philip J. Hepworth; Kevin E. Ashelford; Jason Hinds; Katherine A. Gould; Adam A. Witney; Nicola J. Williams; Howard Leatherbarrow; Nigel P. French; Richard J. Birtles; Chriselle Mendonca; Nick Dorrell; Brendan W. Wren; et al. (Environmental Microbiology, 2011)
Summary Although the major food‐borne pathogen Campylobacter jejuni has been isolated from diverse animal, human and environmental sources, our knowledge of genomic diversity in C. jejuni is based exclusively on human or human food‐chain‐associated isolates. Studies employing multilocus sequence typing have indicated that some clonal complexes are more commonly associated with particular sources. Using comparative genomic hybridization on a collection of 80 isolates representing diverse sources and clonal complexes, we identified a separate clade comprising a group of water/wildlife isolates of C. jejuni with multilocus sequence types uncharacteristic of human food‐chain‐associated isolates. By genome sequencing one representative of this diverse group ( C. jejuni 1336), and a representative of the bank‐vole niche specialist ST‐3704 ( C. jejuni 414), we identified deletions of genomic regions normally carried by human food‐chain‐associated C. jejuni . Several of the deleted regions included genes implicated in chicken colonization or in virulence. Novel genomic insertions contributing to the accessory genomes of strains 1336 and 414 were identified. Comparative analysis using PCR assays indicated that novel regions were common but not ubiquitous among the water/wildlife group of isolates, indicating further genomic diversity among this group, whereas all ST‐3704 isolates carried the same novel accessory regions. While strain 1336 was able to colonize chicks, strain 414 was not, suggesting that regions specifically absent from the genome of strain 414 may play an important role in this common route of Campylobacter infection of humans. We suggest that the genomic divergence observed constitutes evidence of adaptation leading to niche specialization.

Assessment of metal contaminations leaching out from recycling plastic bottles upon treatments - Xiaoliang Cheng; Honglan Shi; Craig D. Adams; Yinfa Ma (Environmental Science and Pollution Research, 2010)

Diffusion Studies of Nanometer Polymersomes Across Tissue Engineered Human Oral Mucosa - Vanessa Hearnden; Hannah Lomas; Sheila MacNeil; Martin Thornhill; Craig Murdoch; Andrew Lewis; Jeppe Madsen; Adam Blanazs; Steve Armes; Giuseppe Battaglia (Pharmaceutical Research, 2009)

Preliminary Examination of How Human-driven Freshwater Flow Alteration Affects Trophic Ecology of Juvenile Snook (Centropomus undecimalis) in Estuarine Creeks - Aaron J. Adams; R. Kirby Wolfe; Craig A. Layman (Estuaries and Coasts, 2009)

Quantification of point‐source groundwater discharges to the ocean from the shoreline of the Big Island, Hawaii - Richard N. Peterson; William C. Burnett; Craig R. Glenn; Adam G. Johnson (Limnology and Oceanography, 2009)
Aerial thermal infrared imaging has revealed that submarine groundwater discharge (SGD) along the western coast of the Big Island of Hawaii is often focused as point‐source discharges that create buoyant groundwater plumes that mix into the coastal ocean. We quantified the SGD fluxes associated with several plumes using natural geochemical tracers. Offshore transects of 222 Rn and 224 Ra show elevated activities and corresponding low salinities in the nearshore waters within the plumes, indicating that these naturally occurring radionuclides can be useful tracers of groundwater inputs in this area. Using a series of simultaneous mass balance equations for water, salt, and radon, we determined the groundwater fluxes of six plumes near Kona, Hawaii. The average SGD fluxes ranged from 1100 m 3 d −1 to 12,000 m 3 d −1 of total (fresh + saline) SGD. The fresh (meteoric) groundwater equivalents for the same flows, modeled by adjusting the groundwater end member to reflect freshwater rather than brackish groundwater composition, ranged from 630 m 3 d −1 to 8600 m 3 d −1 . These fluxes are in general agreement with earlier results obtained by hydrological water budgets and physical oceanographic analyses of fresh SGD rates in this region.

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection - Susanna A. Wood; Lesley L. Rhodes; Serean L. Adams; Janet E. Adamson; Kirsty F. Smith; John F. Smith; H. Robin Tervit; S. Craig Cary (New Zealand Journal of Marine and Freshwater Research, 2008)
A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the long‐term maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long‐term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me 2 SO), at a final concentration of 15% (v/v). Cyanotoxin analysis was undertaken on selected strains known to produce microcystins, nodularin, anatoxin‐a, and saxitoxins. All strains retained their ability to produce these toxins following cryopreservation.

The World Can't Have Wild Tigers and Eat Them, Too - BRIAN GRATWICKE; ELIZABETH L. BENNETT; STEVEN BROAD; SARAH CHRISTIE; ADAM DUTTON; GRACE GABRIEL; CRAIG KIRKPATRICK; KRISTIN NOWELL (Conservation Biology, 2008)

The local introduction of strongly interacting species and the loss of geographic variation in species and species interactions - CRAIG W. BENKMAN; ADAM M. SIEPIELSKI; THOMAS L. PARCHMAN (Molecular Ecology, 2008)
Species introductions into nearby communities may seem innocuous, however, these introductions, like long‐distance introductions (e.g. trans‐ and intercontinental), can cause extinctions and alter the evolutionary trajectories of remaining community members. These ‘local introductions’ can also more cryptically homogenize formerly distinct populations within a species. We focus on several characteristics and the potential consequences of local introductions. First, local introductions are commonly successful because the species being introduced is compatible with existing abiotic and biotic conditions; many nearby communities differ because of historical factors and the absence of certain species is simply the result of barriers to dispersal. Moreover, the species with which they interact most strongly (e.g. prey) may have, for example, lost defences making the establishment even more likely. The loss or absence of defences is especially likely when the absent species is a strongly interacting species, which we argue often includes mammals in terrestrial communities. Second, the effects of the introduction may be difficult to detect because the community is likely to converge onto nearby communities that naturally have the introduced species (hence the perceived innocuousness). This homogenization of formerly distinct populations eliminates the geographic diversity of species interactions and the geographic potential for speciation, and reduces regional species diversity. We illustrate these ideas by focusing on the introduction of tree squirrels into formerly squirrel‐less forest patches. Such introductions have eliminated incipient species of crossbills ( Loxia spp.) co‐evolving in arms races with conifers and will likely have considerable impacts on community structure and ecosystem processes.

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

A New Lithostratigraphic Framework for the Cretaceous Colorado Group in the Cold Lake Heavy Oil Area, East-Central Alberta, Canada - Qiang Tu; Claudia J. Schröder-Adams; Jim Craig (Natural Resources Research, 2007)

Identification of a congenic mouse line with obesity and body length phenotypes - Craig H. Warden; Steven Stone; Sally Chiu; Adam L. Diament; Pablo Corva; Donna Shattuck; Robyn Riley; Steven C. Hunt; Juliet Easlick; Janis S. Fisler; Juan F. Medrano (Mammalian Genome, 2004)

A novel mouse Chromosome 2 congenic strain with obesity phenotypes - Adam L. Diament; Poupak Farahani; Sally Chiu; Janis Fisler; Craig H. Warden (Mammalian Genome, 2004)

Lead, Zinc, Copper, and Cadmium in Fish and Sediments from the Big River and Flat River Creek of Missouri's Old Lead Belt - Nord L. Gale; Craig D. Adams; Bobby G. Wixson; Keith A. Loftin; Yue-wern Huang (Environmental Geochemistry and Health, 2004)

Pedigree‐based assignment tests for reversing coyote ( Canis latrans ) introgression into the wild red wolf ( Canis rufus ) population - Craig R. Miller; Jennifer R. Adams; Lisette P. Waits (Molecular Ecology, 2003)
The principal threat to the persistence of the endangered red wolf ( Canis rufus ) in the wild is hybridization with the coyote ( Canis latrans ). To facilitate idengification and removal of hybrids, assignment tests are developed which use genotype data to estimate identity as coyote, 1 / 4 , 1 / 2 , 3 / 4 or full red wolf. The tests use genotypes from the red wolves that founded the surviving population and the resulting pedigree, rather than a contemporary red wolf sample. The tests are evaluated by analysing both captive red wolves at 18 microsatellite loci, and data simulated under a highly parameterized, biologically reasonable model. The accuracy of assignment rates are generally high, with over 95% of known red wolves idengified correctly. There are, however, tradeoffs between ambiguous assignments and misassignments, and between misidengifying red wolves as hybrids and hybrids as red wolves. These result in a compromise between limiting introgression and avoiding demographic losses. The management priorities and level of introgression determine the combination of test and removal strategy that best balances these tradeoffs. Ultimately, we conclude that the use of the assignment tests has the capacity to arrest and reverse introgression. To our knowledge, the presented approach is novel in that it accounts for genetic drift when the genotypes under analysis are temporally separated from the reference populations to which they are being assigned. These methods may be valuable in cases where reference databases for small populations have aged substantially, pedigree information is available or data are generated from historical samples.

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

Region Specific Modeling of Cardiac Muscle: Comparison of Simulated and Experimental Potentials - Adam L. Muzikant; Edward W. Hsu; Patrick D. Wolf; Craig S. Henriquez (Annals of Biomedical Engineering, 2002)

Cell-specific activation of the HB-EGF and ErbB1 genes by stretch in primary human bladder cells - Hiep T. Nguyen; John M. Park; Craig A. Peters; Rosalyn M. Adam; Anna Orsola; Anthony Atala; Michael R. Freeman (In Vitro Cellular & Developmental Biology - Animal, 1999)

Cryptic diversity in an endemic rainforest skink (Gnypetoscincus queenslandiae) - Craig Moritz; Leo Joseph; Mark Adams (Biodiversity and Conservation, 1993)